Genetic Polymorphism of Cytochrome p450 (2C9) Enzyme in Iranian Baluch Ethnic Group - Tabari, Mojdeh Ghiyas (Open Biochem J, 2015)
The aim of the present study is to assess and compare the frequencies of the cytochrome P450 CYP2C9 variations in the Baluch ethnic group (n=110) with other ethnic groups. The allele frequencies of CYP2C9*1, CYP2C9*2 and CYP2C9*3 were 80.90%, 11.82% and 7.27%, respectively. 70.90%, 11.82%, 8.18%, 4.55%, 2.73% and 1.82% of subjects were with CYP2C9*1/*1, CYP2C9*1/*2, CYP2C9*1/*3, CYP2C9*2/*2, CYP2C9*2/*3 and CYP2C9*3/*3 genotypes, respectively. Different mutants may effect on prediction of drug dose requirements in different ethnic groups. Thus, CYP2C9 variants to be determined for findings high risk groups use optimal dosage of drugs metabolized by this polymorphic enzyme.